Run with the horses eaudiobook The quest for life at its best. - Peterson, Eugene (christianaudio, 2005)
If you have raced with men on foot, and they have wearied you, how will you compete with horses? Jeremiah 12:5 // We all long to live life at its best—to fuse freedom and spontaneity with purpose and meaning. Why then do we often find our lives so humdrum, so unadventuresome, so routine? Or else so frantic, so full of activity, but still devoid of fulfillment? How do we learn to risk, to trust, to pursue wholeness and excellence—to run with the horses in the jungle of life? // In a series of profound reflections on the life of Jeremiah the prophet, Eugene Peterson explores the heart of what it means to be fully and genuinely human. His writing is filled with humor and self-reflection, insight and wisdom, helping to set a course for others in the quest for life at its best.